2016
DOI: 10.1111/trf.13649
|View full text |Cite
|
Sign up to set email alerts
|

Cryoprecipitate indications and patterns of use in the pediatric intensive care unit: inappropriate transfusions and lack of standardization

Abstract: Our study demonstrates a lack of standardization for the use of cryoprecipitate in critically ill children, including many inappropriate transfusions at higher-than-recommended dosing. Prospective randomized clinical trials are warranted to help determine appropriate indications and efficacious cryoprecipitate dosing in the pediatric population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…The number of participants being either "quite confident" or "very confident" before and after access to the app was 10 of 41 (24.4%) and 38 of 41 (92.7%), respectively ( 13,14 platelets, 15 cryoprecipitate). 16,17 Indications for these components are more obscure to the average doctor, and improved guidance is even more essential.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of participants being either "quite confident" or "very confident" before and after access to the app was 10 of 41 (24.4%) and 38 of 41 (92.7%), respectively ( 13,14 platelets, 15 cryoprecipitate). 16,17 Indications for these components are more obscure to the average doctor, and improved guidance is even more essential.…”
Section: Resultsmentioning
confidence: 99%
“…It has previously been demonstrated that simple paper‐based process interventions that require guideline review can improve RBC prescribing, dramatically reduce the total number of units used and increase transfusion appropriateness 2 . The literature contains less information about other blood components, but where reported, studies show equal scope for improvement in adherence to guidelines (FFP, 13,14 platelets, 15 cryoprecipitate) 16,17 . Indications for these components are more obscure to the average doctor, and improved guidance is even more essential.…”
Section: Discussionmentioning
confidence: 99%
“…One study looked at same‐day multicomponent transfusions in paediatric intensive care patients (DeSimone et al, ). The investigators found that the prevalence of co‐transfusions of cryoprecipitate with another blood component ranged from 45·5 to 61·4%, with the most common combination being FP and cryoprecipitate (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, evidence is emerging that point‐of‐care tests do not accurately reflect fibrinogen concentrations, which may explain some of the conflicting results previously reported 24 . Finally, recent transfusion audits have estimated that up to 24% of cryoprecipitate is transfused inappropriately in relation to current transfusion guidelines 25,26 …”
Section: Discussionmentioning
confidence: 99%